PENGARUH LEVERAGE, UKURAN PERUSAHAAN, FIX ASSETS INTENSITY DAN INVESTMENT OPPORTUNITY TERHADAP NILAI PERUSAHAAN DENGAN REVALUASI ASET SEBAGAI VARIABLE MODERATING - Dharmendra Dharmendra; Yunianto Dwi Prasetyo; Warseno Warseno; Susmita Handayani (Pusat Riset dan Inovasi Nasional, 2021)
The purposes of this research is to analyze the influence of leverage, fix asset intensity, investment opportunity and revaluation of fixed asset in Manufacturing Company Consumer Goods Sector in simultaneous and partial. Methods of analysis using moderated regression analysis. Population used is the Manufacturing Company Consumer Goods Sector 2012-2015. Purposive sampling is the technique that is used as a sampling technique with predetermined criteria the number of observations of 112 sampel. The results of this study is only partially the four variables are found to significantly affect the firm value, they are leverage, size, fix asset intensity and investment opportunity. As for revaluation of fixed assets proved to be not significantly affected. Simultaneously the results showed the fifth variable fit or match the data. Revaluation of fixed assets variable as a significant moderating effect was not proven. The findings of this study was that Revaluation of fixed assets variable as a significant moderating effect was not proven to leverage, size, fix asset intensity and investment opportunity. IAS 16 provides options for companies to apply cost or revaluation model.